OP0146 Decrease in cardiovascular event excess risk in rheumatoid arthritis since 2000': a meta- analysis of controlled studies. (15th June 2017) - Filhol, E; Gaujoux-Viala, C; Combe, B; Morel, J; Hua, C; Nutz, A; Lukas, C; Flaisler, F
Abstract : Background: Compared with the general population, patients with rheumatoid arthritis (RA) have an increased risk of cardiovascular disease or events (CE): stroke, Myocardial Infarction (MI), Congestive Heart Failure (CHF) and Cardiovascular Mortality (CVM). Systemic inflammation is the cornerstone of both RA and atherosclerosis. Over the past fifteen years, new treatment strategies such as tight control, treat to target, methotrexate optimization, biologic DMARDs use has allowed a better control of this inflammation. Objectives: The aim of this systematic review was to assess the excess risk of presenting a CE in RA patients as compared to general population, before and after the 2000s. Methods: We systematically searched literature (via Pubmed, Cochrane and abstracts from recent ACR and EULAR congresses) up to March 2016 for observational studies providing data about the occurrence of a CE (among stroke, MI, CHF, CVM) in patients with RA and in a control group. A meta-analysis of the relative risk (RR) concerning patients with RA in relation to the control group was performed for each cardiovascular event and for each period (before and after the 2000s). Results: Out of 5714 screened references, 28 studies were included. For studies published before 2000, an increased risk of CEs was observed in RA patients: – RR=1.12 [95% CI 1.04; 1.21], p=0.002 for stroke – RR=1.25 [1.14; 1.37], p<0.00001 for CHF – RR=1.21 [1.15; 1.26], p<0.00001 for CVM – RR=1.32 [1.24; 1.41], p<0.00001) for MI. For all studies published after the year 2000, the increased risk was not retrieved for CHF (RR=0.58 [0.11; 3.55], p=0.52) and CVM (RR=1.07 [0.74; 1.56], p=0.71). The excess risk of MI was reduced in comparison with the period before 2000: RR=1.18 [1.14; 1.23], p<0.00001.The excess risk of stroke was stable: RR=1.23 [1.06; 1.43], p=0.006. Discussion: This meta-analysis confirms an increased risk of CEs among people with RA relative to the general population. It also appears that this excess risk is less prevalent than prior to 2000s. This might have two explanations: a better management of the cardiovascular risk in patients with RA and a better control of chronic systemic inflammation thanks to new therapeutic strategies. Conclusions: The cardiovascular excess risk of RA patients relative to the general population has decreased since 2000s. This suggests that the recent improvements in RA management may have a positive impact on cardiovascular comorbidities. Disclosure of Interest: None declared